High frequency small signal modeling of CNTFET - Farhana, Soheli; Alam, A. H. M. Zahirul; Khan, Sheroz (2013)
In this paper, we describe the development of small signal model of a CNTFET. The development consist of high frequency response of CNTFET. The CNTFET generates higher output rather than the conventional Si MOSFET. An SPICE model for enhancement mode Carbon nanotube transistor has been developed. The performance analysis of the CNTFET shows the desirable performance parameter in terms of 10 Thz frequency with 1.8 mS.